مستوى النشاط البدني لدى المراة في ضوء الحجر الصحي - براهيمي, مروة; هاشيمي, فاطمة (Institut d’Éducation Physique et Sportive mostaganem 2019/2020, 2019)
الملخص: هدفت الدارسة إلى معرفة مستوى النشاط البدني لدى الم رة في ظل الحجر الصحيأ، مع مقارنة هذا المستوى بين مع المرآة العاملة وغير العاملة .ولتحقيق ذلك تم استخدام المنهج الوصفي لملاءمته مع طبيعة الدارسة على العينة العشوائية المتضمنة 57 امأرة عاملة و57 امأرة غير عاملة. حيث استخدمت استمارة قياس مستوى النشاط البدني للهازع محمد هازع )2014(، وبعد تحليل النتائج المتحصل توصلت الباحثتين إلى: - مستوى النشاط البدني لدى المرآة العاملة غير نشط بما فيه الكفاية - مستوى النشاط البدني لدى المرآة غير العاملة نشط - يوجد فروق في مستوى النشاط البدني لدى المرآة العاملة وغير العاملة في ظل الحجر الصحي لصالح المرآة غير العاملة الماكثة في البيت The study aimed to find out the level of physical activity of the woman under quarantine, while comparing this level with the working and non-working woman. To achieve this, the descriptive approach was used to suit the nature of the study on a random sample of 57 working women and 57 non-working women. Where a form was used to measure the level of physical activity by Al-Hazza Muhammad Hazaa (2014), and after analyzing the results obtained, the researchers concluded: - The level of physical activity of the working woman is not sufficiently active. - The level of physical activity in the inactive woman is active - There are differences in the level of physical activity for a working and non-working woman, under quarantine, in favor of a nonworking woman (staying at home)
LAPA2020-08
Keywords: مستوى النشاط البدني- المراة - ضوء الحجر الصحي